BRANDING IN POLITICS PADA PEMILU 2014 - Syaefurachman Al Banjari (Jurnal Visi Komunikasi, 2014)
Brand is always emotional, especially in politics. Political brand must go beyondtheory and identify the emotional drivers of its target audience and use tough-mindedstrategies and positioning to steal market share (especially audience’s mind and heart share)from the competition. Stealing Mind and Heart Share has developed a unique process unlikeany other brand company in the world that is designed with a single purpose, to steal marketshare. The tactics of emotional branding have evolved over time as consumers have becomemore sophisticated. We’re emotional beings, and we respond to emotional appeals. That’swhy political brand and politicians are much more effective telling stories than quotingstatistics. The statistics may be correct, but the stories ring true. They have to win people’shearts instead of their minds. All brands and its elements can leverage the power ofpersonality to strengthen its appeal. It can only add to the power of a differentiatedpositioning.Merek selalu emosional , terutama dalam politik . merek politik harus melampauiteori dan mengidentifikasi driver emosional audiens target dan menggunakan strategi kerashati dan positioning untuk mencuri pangsa pasar ( pikiran terutama penonton dan berbagi hati) dari kompetisi . Mencuri Pikiran dan Hati Berbagi telah mengembangkan proses unik tidakseperti merek perusahaan lain di dunia yang dirancang dengan tujuan tunggal , untuk mencuripangsa pasar . Taktik emotional branding telah berevolusi dari waktu ke waktu sebagaikonsumen telah menjadi lebih canggih . Kami makhluk emosional , dan kami menanggapibanding emosional . Itu sebabnya merek politik dan politisi yang jauh lebih efektif berceritadari statistik mengutip . Statistik mungkin benar , tapi cerita berdering benar . Mereka harusmemenangkan hati rakyat bukan pikiran mereka . Semua merek dan unsur-unsurnya dapatmemanfaatkan kekuatan kepribadian untuk memperkuat daya tariknya . Ini hanya dapatmenambah kekuatan positioning dibedakan